"You give me a name that I cannot say": an investigation into the intelligibility of the criterial rules in the theoretical component of CAPS Grade 10-12 visual art - Palte, Lauren Nicole (School of Education, 2023)
Previous work in the field of art education in South Africa has addressed the need to make explicit the requirements and valued criteria in the practical work (Bolton, 2006). However, systematic research into the theoretical component of the National Curriculum Statement Curriculum and Assessment Policy Statement (CAPS) for Visual Arts in the Further Education and Training Phase has yet to be conducted. This study teases out the relationship between knowledge and skills that remains under-theorised in the expression of visual literacy in the curriculum. Developed in fields adjacent to Art History and Visual Culture Studies, the literature defines visual literacy in generic terms that describe what a visually literate person can do. Visual literacy requires consideration when translated into a method for a subject that has its roots in a disciplinary tradition, in this case, Art History. The literature on visual literacy places emphasis on the positionality of the viewer and the tacit nature of acquisition which differs from specialised knowledge about the artist's context of production that is studied in Art History. The framing of knowledge and skills in the curriculum requires careful theorisation to determine whether subjective or specialised communication is privileged and the nature of acquisition. I conducted a document analysis to show the type of communication valued in two questions of the Department of Basic Education National Senior Certificate Grade 12 Paper 1 examinations and memoranda over three years. I considered the knowledge and skills transmitted by the CAPS curriculum for Visual Art Grades 10-12 and whether they align with the expectations of the questions and memoranda. I make recommendations for the curriculum, assessment and memoranda based on these observations to contribute to the conversation about pupil performance in Visual Art at Grade 12 level.